Efforts To Improve Cooling Water Treatment On The Performance Of Master Engines On Ship KM. Camara Nusantara 1 - Kodrat Alam; Monica Amanda; Dimas Pratama Yuda; Muhamad Fahmi Amrillah (IWJ : Inland Waterways Journal, 2023)
The cooling system is a medium that serves to absorb heat. The heat is obtained from the combustion of fuel in the cylinder. engine cooling is intended to maintain a stable temperature in the engine so that there is no too high temperature increase as a result of the combustion of fuel in the cylinder and the friction that occurs. Cooling the engine is also intended to reduce the risk of damage. The diesel engine cooling system is divided into 2, namely a closed cooling system and an open cooling system. The open cooling water system has an average temperature of 300 Celsius and the closed cooling water system has an average inlet temperature of 400 Celsius and an outlet temperature of 700-800 Celsius. Problems that often occur in the cooling water system are broken shaft impellers for seawater pumps, pipe leaks and capillary pipes clogged with dirt. The results of the writing refer to the damage to these components, this causes the fresh water temperature to rise. Therefore, regular and systematic maintenance and repair of these components is absolutely necessary for the cooling system to work optimally.